Miniature chicken ileal explant culture to investigate the inflammatory response induced by pathogen-associated molecular patterns - Mátis, Gábor; Sebők, Csilla; Horváth, Dávid G.; Márton, Rege Anna; Mackei, Máté; Vörösházi, Júlia; Kemény, Ágnes; Neogrády, Zsuzsanna; Varga, Ilona; Tráj, Patrik (Frontiers in Veterinary Science, 2025)
Gastrointestinal inflammation leads to maldigestion and systemic diseases in poultry. To tackle the problem of the industry and to search for therapeutic candidates in vitro models are inevitable. Both immersion and air-liquid interface explant models are available, although there is limited information on the size-dependent applicability and response to different pathogen-associated molecular patterns (PAMPs) in the case of these model systems. The study aimed to compare the morphology and viability of miniature chicken gut explant cultures obtained with a biopsy punch to examine the size-dependent change over time. To verify the applicability of the model, pathogen-associated molecular patterns (PAMPs): flagellin, lipoteichoic acid (LTA) and polyinosinic polycytidylic acid (poly I:C) were applied to induce inflammation. The 2 mm diameter explants showed a decrease in metabolic activity measured by CCK-8 assay after 12 h and a significantly higher extracellular lactate dehydrogenase activity indicating cellular damage compared to the 1 mm explants, supported by histological differences after 24 h of culturing. After 12 h of incubation, the 1.5 mm explants retained columnar epithelial lining with moderate damage of the lamina propria (H&E and pan-cytokeratin staining). Exposure to 100 μg/mL poly I:C reduced the metabolic activity of the 1.5 mm explants. LTA and poly I:C increased IFN-γ concentration at both applied doses and IFN-α concentration was elevated by 50 μg/mL poly I:C treatment. Flagellin administration raised IL-2, IL-6, and RANTES levels, while higher LTA and poly I:C concentrations increased the IFN-γ/IL-10 ratio. According to the observations, the viability and integrity of the explants decreases with their size. After 12 h, the 1.5 mm diameter miniature chicken ileal explant stimulated with PAMPs can be an appropriate model to mimic diseases involving tissue damage and inflammation.